2021
DOI: 10.3390/w13081075
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Spatiotemporal Variations of Soil Salinization and Its Relationship with Eco-Hydrological Parameters at the Regional Scale in the Kashi Area of Xinjiang, China from 2000 to 2017

Abstract: Soil salinization is one of the most serious issues of land degradation, especially in inland drylands, such as the Kashgar region in the Xinjiang province, western China. The investigation of the spatiotemporal variations of soil salinization and its causes is critical for regional ecological restoration and social development. In this study, salinization severity was firstly interpreted in Kashgar region for the years 2000, 2010, and 2017 using multitemporal Landsat images, and the spatiotemporal variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In this paper, n = 4. The salinization severity index (S i ) is used to characterize the spatio-temporal distribution of regional soil salinity [25]:…”
Section: Spatial and Temporal Distribution Characteristics Of Soil Sa...mentioning
confidence: 99%
“…In this paper, n = 4. The salinization severity index (S i ) is used to characterize the spatio-temporal distribution of regional soil salinity [25]:…”
Section: Spatial and Temporal Distribution Characteristics Of Soil Sa...mentioning
confidence: 99%
“…Soil salinization is one of the most serious problems of land degradation [1], UNESCO and FAO have reported that 954 million hectares of worldwide land was disturbed by salinization [2]. Salinization is not only considered as an environmental issue but has developed to an economic problem [3], it gradually becomes a great challenge restricting the development of agriculture and husbandry [4].…”
Section: Introductionmentioning
confidence: 99%
“…The problems faced by agriculture today, such as soil salinization, irrigation water shortage, and groundwater pollution, have increased with the increase in the global population 1‐3 . Nitrogen (N) brings benefits but also has serious negative effects 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…The problems faced by agriculture today, such as soil salinization, irrigation water shortage, and groundwater pollution, have increased with the increase in the global population. [1][2][3] Nitrogen (N) brings benefits but also has serious negative effects. 4,5 In particular, soil N leaching was one of the main sources of environmental pollution and human diseases, such as loss of biological diversity, eutrophication, 6,7 infantile methemoglobinemia, and cancer of the digestive tract.…”
Section: Introductionmentioning
confidence: 99%